A View of Personality a Good Language Learner: An Investigation of Non-EFL Students - Tira Nur Fitria (Abjadia, 2022)
The personality of the learner is one of the suspected internal factors that affect the success of foreign language learning. The objective of this study is to investigate the personality of non-EFL students to be being good language learners. This research is descriptive qualitative. The questionnaire is used to determine the students’ MBTI personality type (Myers-Briggs Type Indicator). The analysis shows that the personality of the student’s initial name SK is introverted, intuition, feeling, and judging.  While, the personality of the student’s initial name MT is extraverted, sensing, thinking, and perceiving. The personality type of Initial’s Student Named MT is INFJ (The Counselor). This personality shows the characters insightful, harmonious, compassionate, private, ad perceptive. While the personality type of Initial’s Student Named SK is ESFP (The Performer). This personality shows the characters energetic, dynamic, earnest, charming, and optimistic. The personality of the learner is one of the factors that need to be considered in foreign language learning that can support or even inhibition of learning success. Learners need to know their personality better to know their strengths and weaknesses regarding language learning. The characteristics of a good language learner need to be known to be a good foreign language learner. Future research still required larger samples and more comprehensive personality measures (possibly using more than one of the standard multi-trait model assessments with the same or different students) to find precise statistical evidence that will shed light on teachers'/lecturer views/beliefs about the importance of this issue.